Autonomic dysfunction in muscular dystrophy: a theoretical framework for muscle reflex involvement - Smith, Scott A.; Downey, Ryan M.; Williamson, Jon W.; Mizuno, Masaki (Frontiers in Physiology, 2014)
Muscular dystrophies are a heterogeneous group of genetically inherited disorders whose most prominent clinical feature is progressive degeneration of skeletal muscle. In several forms of the disease, the function of cardiac muscle is likewise affected. The primary defect in this group of diseases is caused by mutations in myocyte proteins important to cellular structure and/or performance. That being stated, a growing body of evidence suggests that the development of autonomic dysfunction may secondarily contribute to the generation of skeletal and cardio-myopathy in muscular dystrophy. Indeed, abnormalities in the regulation of both sympathetic and parasympathetic nerve activity have been reported in a number of muscular dystrophy variants. However, the mechanisms mediating this autonomic dysfunction remain relatively unknown. An autonomic reflex originating in skeletal muscle, the exercise pressor reflex, is known to contribute significantly to the control of sympathetic and parasympathetic activity when stimulated. Given the skeletal myopathy that develops with muscular dystrophy, it is logical to suggest that the function of this reflex might also be abnormal with the pathogenesis of disease. As such, it may contribute to or exacerbate the autonomic dysfunction that manifests. This possibility along with a basic description of exercise pressor reflex function in health and disease are reviewed. A better understanding of the mechanisms that possibly underlie autonomic dysfunction in muscular dystrophy may not only facilitate further research but could also lead to the identification of new therapeutic targets for the treatment of muscular dystrophy.